Cardiac myosin inhibitors: Efficacy, safety and future directions of aficamten in hypertrophic obstructive cardiomyopathy - Ikponmwosa Jude Ogieuhi; Victor Oluwatomiwa Ajekiigbe; Boluwaduro Abasiekem Adeyemi; Bright Nwatamole; Komolafe Babajide Ayodeji; Oshomoh Mark-Anthony Ugiomoh; Temiloluwa Adebayo Odeniyi; Adewunmi Akingbola; Efosa Peace Iyawe; Olabode Olawale Oladejo; Motunrayo Oluwatoyosi Lawal; Nathnael Abera Woldehana; et al. (The Egyptian Heart Journal)
Abstract Background Hypertrophic obstructive cardiomyopathy (HOCM) is a genetic disorder that affects the cardiac myocytes leading to asymmetric hypertrophy of the left ventricle and obstruction of the left ventricular outflow tract (LVOT) with possible risk of sudden cardiac death in some high-risk patients. This paper aims to evaluate the efficacy, safety, and future prospects of aficamten in the management of HOCM and its potential to transform current standards of care. Main Body Over the years, there have been significant milestones in HOCM management, including pharmacological and surgical techniques, which have reduced the morbidity and mortality associated with this disease. However, HOCM remains a challenging disease to manage for healthcare providers due to the heterogeneous nature of its presentation and limitations to the conventional treatment medications including beta blockers and non-dihydropyridine calcium channel blockers. These traditional options often provide inadequate symptomatic relief and have significant side effects. Surgical options such as septal ablation have shown positive outcomes but are associated with procedural risks. Therefore, recent advancements have led to the development of novel agents such as cardiac myosin inhibitors (CMIs). Conclusion Aficamten is a new second-generation cardiac myosin inhibitor (CMI) that has shown promising results from clinical trials. With reports of reduced LVOT obstruction and improvement in heart failure symptoms, these findings indicate potential improvement in the quality of life of patients with HOCM. Graphical Abstract